2017
DOI: 10.3803/enm.2017.32.1.115
|View full text |Cite
|
Sign up to set email alerts
|

Lobeglitazone, a Novel Peroxisome Proliferator-Activated Receptor γ Agonist, Attenuates Renal Fibrosis Caused by Unilateral Ureteral Obstruction in Mice

Abstract: BackgroundRenal tubulointerstitial fibrosis is a common feature of the final stage of nearly all cause types of chronic kidney disease. Although classic peroxisome proliferator-activated receptor γ (PPARγ) agonists have a protective effect on diabetic nephropathy, much less is known about their direct effects in renal fibrosis. This study aimed to investigate possible beneficial effects of lobeglitazone, a novel PPARγ agonist, on renal fibrosis in mice.MethodsWe examined the effects of lobeglitazone on renal t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 33 publications
2
10
0
Order By: Relevance
“…Collagen-1 (Col-1) is the main component of ECM, which is closely related to cell growth, differentiation, proliferation, repair of tissue injury and inflammation, sclerosis, and fibrosis. Abnormal synthesis of Col-I can increase the production of reactive oxygen species (ROS) in DN and can increase the level of oxidative stress, resulting in progressive glomerular injury [17, 18]. IL-1 β can also regulate the proliferation of mesangial cells, the production of ECM, and renal fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Collagen-1 (Col-1) is the main component of ECM, which is closely related to cell growth, differentiation, proliferation, repair of tissue injury and inflammation, sclerosis, and fibrosis. Abnormal synthesis of Col-I can increase the production of reactive oxygen species (ROS) in DN and can increase the level of oxidative stress, resulting in progressive glomerular injury [17, 18]. IL-1 β can also regulate the proliferation of mesangial cells, the production of ECM, and renal fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of diabetes is increasing substantially worldwide, mainly due to increasing rates of obesity and insulin resistance [ 37 38 39 40 ], as well as in the increasing number of elderly people, in whom fracture is a critical factor affecting quality of life and mortality [ 2 ]. Under these circumstances, TZDs will continue to play a crucial role in diabetes management, and awareness of both the beneficial and side effects of these drugs is important in daily clinical practice [ 41 ]. In this study, treatment of lobeglitazone 0.5 mg once a day for 52 weeks showed no detrimental effect on BMD at the femur neck and total hip area compared to placebo.…”
Section: Discussionmentioning
confidence: 99%
“…PPARγ was initially identified through its role in the regulation of glucose and lipid metabolism and cell differentiation, but it is now well established that PPARγ agonists are also exhibit anti‐inflammatory and anti‐fibrotic effects (Clark, ; Dantas et al ., ). In this regard, PPARγ is a regulator of connective tissue homeostasis, and different experimental approaches have shown that PPARγ ligands attenuate hepatic (Galli et al ., ), renal (Bae et al ., ) and pulmonary fibrosis (Milam et al ., ) as well as bleomycin‐induced skin fibrosis (Gonzalez et al ., ; Wei et al ., ; del Rio et al ., ; Ruzehaji et al ., ).…”
Section: Introductionmentioning
confidence: 99%